2022
DOI: 10.1371/journal.pntd.0010810
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of different drugs and treatment regimen for hookworm on cure and egg reduction rates taking into account diagnostic error

Abstract: Background Hookworm infections, caused by Ancylostoma duodenale and Necator americanus, are of considerable public health importance. The World Health Organization recommends preventive chemotherapy as the key strategy for morbidity control. Meta-analyses have been conducted to estimate treatment efficacy of available drugs and drug combinations. However, in most studies, the relation between the diagnostic error and infection intensity have not been considered, resulting in an overestimation of cure rates (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similar to false-positive results, false-negative Kato-Katz thick smears that contained a larger number of eggs were probably due to technical skill [20]. The previous reports have shown that readers might be tired due to the high number of thick Kato-Katz smears read per day [21][22][23]. Therefore, a single Kato-Katz thick smear has low sensitivity, and the proportion of false-negative diagnoses is usually assessed [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 98%
“…Similar to false-positive results, false-negative Kato-Katz thick smears that contained a larger number of eggs were probably due to technical skill [20]. The previous reports have shown that readers might be tired due to the high number of thick Kato-Katz smears read per day [21][22][23]. Therefore, a single Kato-Katz thick smear has low sensitivity, and the proportion of false-negative diagnoses is usually assessed [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 98%